UPAYA GURU DALAM MENGATASI TUNA CAKAP BELAJAR PADA SISWA KELAS V DI SD NEGERI 02 SENDOYAN - Patriana Patriana; Nura Rizqia (CV. ADIBA AISHA AMIRA, 2024)
The purpose of this study was to find out the types of student learning disabilities, the factors that cause student learning disabilities, and how the teacher's efforts to overcome the learning disability of fifth grade students at SD Negeri 02 Sendoyan. This type of research is descriptive qualitative. Data collection methods in this study are observation and interviews. The results showed that students with learning disabilities were having difficulty concentrating, being bored in learning, slow in accepting subject matter, and low student learning outcomes. The factors that cause disabled students to learn come from the students themselves, as well as factors from outside the students themselves both from the family, school or social environment. While the efforts made by the teacher in overcoming student learning disabilities are (1) providing remedial teaching and enrichment for students whose learning outcomes are below average and students who are slow in accepting subject matter, (2) providing reflection or apperception of students by doing ice breaking and yelling to return students' attention when they have difficulty concentrating, (3) creating a conducive and fun learning atmosphere that involves students actively while studying, and (4) provide guidance and counseling services to students who have deviant behaviors.